Pengaruh Model Pembelajaran Matematika Realistik terhadap Hasil Belajar Siswa Kelas VII di MTs Dakwah Islamiyah Putri - Hasnawati, Anida; Sripatmi; Pramestie Wulandari, Nourma (FKIP Universitas Mataram, 2025)
This study aims to determine the effect of the Realistic Mathematics Education (RME) model on students' learning outcomes. A quantitative approach with a quasi-experimental design was employed. The experimental group received instruction using the RME model, while the control group was taught using direct instruction. The population of this study consisted of all seventh-grade students at MTs Dakwah Islamiyah Putri Nurul Hakim in the 2024/2025 academic year, totaling 126 students divided into four classes. The sample was selected using simple random sampling, resulting in class VII B (32 students) as the experimental group and class VII C (32 students) as the control group. Data were collected using a learning outcome test. Hypothesis testing was conducted using the t-test, which yielded a t-value (tₕitung) of 3.203 and a t-table value (ttabel) of 1.999. Since tₕitung > ttabel, the null hypothesis was rejected, indicating a significant difference in learning outcomes between students taught with the RME model and those taught with direct instruction. The effect size was calculated to be 0.801, which falls into the moderate category. This suggests that the RME model has a meaningful impact on students' mathematics learning outcomes. outcomes of Grade VII students at MTs Dakwah Islamiyah Putri.